Criminal court in action - Barnard, David (London, 1988)
This highly original and popular book has been found as useful by practitioners as by students. It is written by a practising member of the Bar to explain what really happens in a criminal court. Part one illustrates a typical case by reference to all the relevant documentation and transcripts of the committal proceedings and trial. Part two contains a detailed explanation of the rules of criminal procedure as seen from the point of view of the advocate in court. In this edition, the important changes introduced by the Police and Criminal Evidence Act 1984 and the Codes of Practice are considered in detail together with recent developments affecting bail, costs, legal aid and, in Part three, sentencing. The appendix contains all the key statutory provisions and the complete text of the Codes.
Keywords: Criminal procedure-England